SOCIAL RELATIONS OF YAM FLOUR PRODUCTION AND DISTRIBUTION IN LAGOS AND OYO STATES,NIGERIA (2023)
Social Relations (SRs), the network of interactions among members of the society, is a vital component of healthy partnerships among organisations worldwide. Conversely, egoistic motivation for reward and numerous market and institutional failures havechallenged healthy relationships among people in informal organisations in Nigeria. Existing studies on SRs have largely focused on formal organisations with scant attention paid to in informal organisations, especially among actors in yam flour (èlùbọ́)production and distribution. This study, therefore, examined the social relations (social organisation, exchange value construction, value chain activities, indigenous practices and the socio-demographic characterisation) underlying yam flour production anddistribution in Lagos and Oyo states, Nigeria. There is a need for an actor centred policy formulation and implementation by governments. The appropriate authorities should provide more intervention programmes to enhance social relations and yam flourproduction and distribution.